A killer app for computer chat. (Economist, 1999)
Discusses use of software robots or `chatterbots' in dispensing information over the Internet. Response to growth of online businesses and the need for technical support; Suitability of bots for dealing with frequently asked questions; Neuromedia's NeuroServer chatterbot system; Companies developing pattern-matching and case-based reasoning systems.